An experimental evaluation of the blast resistance of heterogeneous concrete-based composite bridge decks. (15th January 2019) - Hajek, Radek; Fladr, Josef; Pachman, Jiri; Stoller, Jiri; Foglar, Marek
Highlights: The blast performance of concrete increases with material heterogeneity. A compact material dissipates less energy within its structure. Controlled heterogeneity predetermines blast damage zones. Layer delamination increases blast energy dissipation. Abstract: Because of the current geopolitical situation, research on improving the resistance of the civil and transport infrastructure to blast or impact loads has gained considerable attention. This paper presents the results of full-scale blast experiments designed to characterize the resistance of concrete-based composite bridge decks subjected to close-in blast loading. Three composite decks with different degrees of heterogeneity were proposed and tested: a slab with basalt fiber meshes in multiple layers along the depth of the specimen, a slab with recycled textile sheets 100 mm in total thickness, and a typical hollow-core prestressed slab. The dependence of the extent of the blast damage on the material characteristics of the composite material was studied. A detailed study of the damage to the specimen caused by the close-in explosion found apparent delamination of all tested composite specimens. The heterogeneity of the layered composite material converts the blast damage due to internal rebounds into layer delamination.